Characteristics of Oxidative Storage Stability of Canola Fatty Acid Methyl Ester Stabilised with Antioxidants - Prakoso, Tirto; Udomsap, Parncheewa; Tanaka, Akiko; Hirotsu, Toshihiro; Goto, Shinichi (Journal of Engineering and Technological Sciences, 2012)
TheÂ  storageÂ  effectsÂ  onÂ  theÂ  oxidationÂ  characteristicsÂ  ofÂ  fattyÂ  acid methyl ester of canola oil (CME) were investigatedÂ  in this study.CME stabilised withÂ  twoÂ  antioxidants, i.e.2,6-di-tert-bytyl-p-cresolÂ  (BHT) and 6,6-di-tert-butyl-2, 2â-methylendi-p-cresolÂ  (BPH),Â  wasÂ  stored at 20, 40 andÂ  60Â°C.TheÂ  oxidation stability dataÂ  were measuredÂ  byÂ  theÂ  Rancimat testÂ  method andÂ  it wasÂ  found Â that both BHT and BPHÂ  addition increasedÂ  the oxidation resistance ofÂ  theÂ  CME.Â  The results showed that when BPH or BHT was added at a concentration of 100 ppm, the oxidation induction period of the neat CME samples increased from 5.53 h to 6.93Â  hand Â 6.14 h,Â  respectively.Â  Comparing both antioxidants,Â  BPHÂ  proved to be moreÂ  effectiveÂ  inÂ  increasingÂ  theÂ  oxidationÂ  resistanceÂ  whenÂ  bothÂ  antioxidants were added at the same concentration.Â  Furthermore, the oxidation induction timedecreasedÂ  linearlyÂ  withÂ  theÂ  storageÂ  time.Â  ItÂ  wasÂ  shownÂ  thatÂ  theÂ  oxidation occurredÂ  rapidlyÂ  inÂ  theÂ  firstÂ  8Â  weeksÂ  ofÂ  storage.Â  Later,Â  aÂ  kineticÂ  studyÂ  was undertakenÂ  andÂ  first-orderÂ  kineticsÂ  wereÂ  appliedÂ  toÂ  explainÂ  theÂ  oxidation characteristics ofÂ  theÂ  CME added with antioxidants. This kinetic study focused onÂ  exploitingÂ  theÂ  activationÂ  energyÂ  values Â obtainedÂ  fromÂ  theÂ  Arrheniusequations. Also, theÂ  oxidation effects onÂ  otherÂ  quality parameters, including acid value, peroxide value, kinematic viscosity, and water content, were examined.